Molecular and quantative analyses of genetic variation in farmed Atlantic salmon - Norris, A. T. (Trinity College (Dublin, Ireland). Department of Genetics, 2003)
Genetic diversity between three farmed and four wild populations and within six 6 year classes of one farmed population of Atlantic salmon were analysed using 15 microsatellite markers. High levels of polymorphism were observed over all populations with average heterozygosity at 0.70. Two farmed salmon populations showed less genetic variability than wild salmon in terms of allelic diversity and heterozygosity. Between farmed populations significant differences were observed in expected heterozygosity suggesting that more intensive breeding practices may have resulted in a further erosion of genetic variability. Phylogenetic analysis using either populations or individuals as nodes show a clustering of populations into two groups, farmed and wild. This suggests that founder effects and subsequent selection have had more effect on the genetic differentiation between these strains than geographical separation.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin